Chromosome topology guides the Drosophila Dosage Compensation Complex for target gene activation. (9th August 2017) - Schauer, Tamás; Ghavi‐Helm, Yad; Sexton, Tom; Albig, Christian; Regnard, Catherine; Cavalli, Giacomo; Furlong, Eileen EM; Becker, Peter B
Abstract: X chromosome dosage compensation in Drosophila requires chromosome‐wide coordination of gene activation. The male‐specific lethal dosage compensation complex (DCC) identifies and binds to X‐chromosomal high‐affinity sites (HAS) from which it boosts transcription. A sub‐class of HAS, PionX sites, represent first contacts on the X. Here, we explored the chromosomal interactions of representative PionX sites by high‐resolution 4C and determined the global chromosome conformation by Hi‐C in sex‐sorted embryos. Male and female X chromosomes display similar nuclear architecture, concordant with clustered, constitutively active genes. PionX sites, like HAS, are evenly distributed in the active compartment and engage in short‐ and long‐range interactions beyond compartment boundaries. Long‐range, inter‐domain interactions between DCC binding sites are stronger in males, suggesting that the complex refines chromatin organization. By de novo induction of DCC in female cells, we monitored the extent of activation surrounding PionX sites. This revealed a remarkable range of DCC action not only in linear proximity, but also at megabase distance if close in space, suggesting that DCC profits from pre‐existing chromosome folding to activate genes. Synopsis: X chromosome loci with binding sites for the Drosophila MSL dosage compensation complex are engaged in long‐range interactions within the active compartment. The constitutive chromosome folding likely facilitates vital gene activation in male flies. Dosage compensation profits from the compartment organization of the X chromosome. Long‐range contacts between loci in the active compartment facilitate interactions between DCC binding sites. The activation of genes correlates with their 3D proximity to DCC binding sites. Abstract : X chromosome loci with binding sites for the Drosophila MSL dosage compensation complex are engaged in long‐range interactions within the active compartment. The constitutive chromosome folding likely facilitates vital gene activation in male flies.